Analyse du processus d’admission en L1 dans les filières universitaires non sélectives - Agathe Dirani; Céline Piquée (Éducation et Socialisation)
Using the data from the French digital platform Parcoursup, which manage students’ applications to higher education, we try to understand the coexistence of different users’ logics in the access to the first year of higher education. The objective is to describe the role played by each other (the students, the secondary pedagogic teams, the members of the higher education selection commission) into the selection procedure. More precisely, we try to examine the fairness of the procedure identifying the justice principles at stake, caught between meritocracy and the human intervention, and its effectivity. The first part of the analyses aims at explaining the tension exercised by the selection commission that propose places into university and the candidates that choose to register. Then for different academic disciplines, we examine the place of the “human intervention”. That to say, we analyze what the formulation of qualitative judgments about applicants, made by the secondary teaching teams and their degree of consideration in the ranking defined by the higher education selection commission do to the application process and its readability. Thus, we put into question the affectation procedure to higher education which is funded on scholar meritocracy but also supposed to be regulated by the “human intervention” of the secondary and higher education scholar stakeholders.